DESKRIPSI KEMAMPUAN PENALARAN MATEMATIS SISWA DITINJAU DARI GAYA BELAJAR DAN GENDER - Eti Nurhayati; Fitrianto Eko Subekti (AlphaMath : Journal of Mathematics Education, 2017)
The objectives of this research was to construct description on student’s mathematical cognitive ability in SMP Muhammadiyah Sumbang viewed from learning style and gender on topic of rectangular. The research method was descriptive qualitative. The research population was students of 7th Grade A and D with purposive sampling technique. Students were divided into six groups and two students from each group were selected as respondents. Test, interview and documentation were used as the data collection. The results indicated: 1) Male and female students with visual learning style could not have knowledge of five indicators of mathematical cognitive ability as follow: to propose presumption, to make mathematical manipulation, to draw conclusions, to construct evidence, to give reasonable evidence for solutions, to examine argument validity, and to find path of mathematical indication. 2) Male and female students with auditory learning style could have knowledge one indicator of mathematical cognitive ability as of to find path of mathematical indication. 3) Male students with kinesthetic learning style could have knowledge of one indicator of mathematical cognitive ability as of to make mathematical manipulation. 4) Female students with kinesthetic learning style could have knowledge of one indicator of mathematical cognitive ability as of to propose presumption. KEY WORDS: Mathematical cognitive ability, Learning style, Gender